Evaluation of the preclinical efficacy of four antivenoms, distributed in sub-Saharan Africa, to neutralize the venom of the carpet viper, Echis ocellatus, from Mali, Cameroon, and Nigeria. (November 2015) - Sánchez, Laura V.; Pla, Davinia; Herrera, María; Chippaux, Jean Philippe; Calvete, Juan J.; Gutiérrez, José María
Abstract: Snakebite envenoming causes a heavy toll in sub-Saharan Africa in terms of mortality and sequelae. In the West African savannah, the viperid Echis ocellatus is responsible for the vast majority of bites. In the last decades, several new antivenoms have been introduced for the treatment of these envenomings, although the assessment of their preclinical efficacy against the venom of E. ocellatus has been studied only for some of them. This work analyzed comparatively the ability of four antivenoms (FAV Afrique, EchiTAb G, EchiTAB-Plus-ICP ®, and Inoserp™ Panafricain) to neutralize lethal, hemorrhagic, and in vitro coagulant activities of the venoms of E. ocellatus from Mali, Cameroon, and Nigeria. In addition, an immunoaffinity chromatography antivenomic protocol was used to assess the ability of the four antivenoms to bind to the proteins of these venoms. Results showed that all the antivenoms were effective in the neutralization of the three effects investigated, and were able to immunocapture, completely or partially, the most abundant components in the E. ocellatus venoms from the geographical origins sampled. Our observations also highlighted quantitative differences between antivenoms in their neutralizing and antivenomics profiles, especially regarding neutralization of in vitro coagulant activity, suggesting that different doses of these antivenoms are probably needed for an effective treatment of human envenomings by this species. Graphical abstract: Highlights: Four antivenoms were evaluated against venoms of Echis ocellatus . Neutralization of lethal, hemorrhagic and coagulant activities were studied. Recognition of venom toxins was performed by antivenomics. All antivenoms were effective with quantitative variations between them. It is suggested that different doses should be used at the clinical setting.